The The Influence of the Islamic Entrepreneurship Spiritual Perspective, Islamic Entrepreneurship Business Perspective, and E-Commerce Adoption on Business Performance among Muslim Women Entrepreneurs - Tsaqyfa, Mazaya Najmy; Ridlwan, Ahmad Ajib; Susilowati, Fitriah Dwi; Timur, Yan Putra (State of Islamic Institute Langsa, 2025)
The development of digital technology and the values of Islamic entrepreneurship can serve as an important foundation for improving business performance, particularly for Muslim women entrepreneurs. However, in reality, many business actors still face limitations in optimally integrating spiritual perspectives, Islamic business ethics, and the use of digital technology. This study aims to analyze the influence of Islamic Entrepreneurship Spiritual Perspective, Islamic Entrepreneurship Business Perspective, and E-Commerce Adoption on Business Performance among Muslim women entrepreneurs in Surabaya. The research methodology employs a quantitative approach with primary data obtained through the distribution of online questionnaires. The sampling technique used is purposive sampling with a total of 129 respondents. Data analysis was conducted using Structural Equation Modeling – Partial Least Square (SEM-PLS) with the SmartPLS 4.0 software. The findings indicate that the Islamic Entrepreneurship Spiritual Perspective, Islamic Entrepreneurship Business Perspective, and E-Commerce Adoption have a positive effect on Business Performance among Muslim women entrepreneurs in Surabaya.